Aire and Fezf2, two regulators in medullary thymic epithelial cells, control autoimmune diseases by regulating TSAs: Partner or complementer? - Qi, Yanfei; Zhang, Rongchao; Lu, Yaoping; Zou, Xueyang; Yang, Wei (Frontiers in Immunology, 2022)
The expression of tissue-specific antigens (TSAs) in medullary thymic epithelial cells (mTECs) is believed to be responsible for the elimination of autoreactive T cells, a critical process in the maintenance of central immune tolerance. The transcription factor autoimmune regulator (Aire) and FEZ family zinc finger 2(Fezf2) play an essential role in driving the expression of TSAs in mTECs, while their deficiency in humans and mice causes a range of autoimmune manifestations, such as type 1 diabetes, Sjögren's syndrome and rheumatoid arthritis. However, because of their regulatory mechanisms, the expression profile of TSAs and their relationship with special autoimmune diseases are still in dispute. In this review, we compare the roles of Aire and Fezf2 in regulating TSAs, with an emphasis on their molecular mechanisms in autoimmune diseases, which provides the foundation for devising improved diagnostic and therapeutic approaches for patients.